MUC1 peptide-loaded dendritic cell vaccine boosts antitumor immunity in pancreatic cancer - Xie, Huiping; Yang, Wenzhuo; Chen, Haodong; Zhang, Zhilan; Zhao, Zelin; Jin, Yuanyuan; Fan, Shuai; Yang, Zhaoyong (Frontiers in Immunology, 2026)
ObjectivePancreatic cancer is one of the most aggressive malignancies with a poor prognosis and limited treatment options. This study aimed to evaluate the efficacy of a dendritic cell (DC) vaccine pulsed with mucin 1 (MUC1) peptide antigens in the immunotherapy of pancreatic cancer.MethodsMononuclear cells were isolated from umbilical cord blood and induced to differentiate into DCs. The surface markers of DCs and their phagocytic capacity for FITC-OVA were detected using flow cytometry. The stimulatory effect of DC vaccines loaded with MUC1 antigen peptides (568 and 619) on T lymphocyte proliferation was assessed by CCK-8 assay. ELISA was used to measure the secretion of IL-12p70 by DCs and IFN-γ production by activated cytotoxic T lymphocytes (CTLs). The proportion of CD8+ and CD4+ cells among CTLs activated by the DC vaccine was analyzed via flow cytometry. The cytotoxic activity of activated T cells against pancreatic cancer cell lines was evaluated using an LDH release assay. Furthermore, bioinformatic analysis was performed to compare MUC1 expression between pancreatic cancer and normal tissues and its correlation with patient prognosis. Western blot was used to detect MUC1 expression in pancreatic cancer cell lines. The antitumor effect of the DC vaccine pulsed with antigen peptide 619 was investigated in a humanized huHSC-M-NSG mouse model of pancreatic cancer.ResultsImmature DCs (imDCs) highly expressed CD11c, HLA-DR, and CD86, but weakly expressed CD14; mature DCs (mDCs) highly expressed CD11c, HLA-DR, CD83, CD80, and CD86, and weakly expressed CD14. DCs on day 5 of culture exhibited the strongest phagocytic capacity for FITC-OVA. DC vaccines loaded with either MUC1 peptide 568 or 619 significantly promoted T lymphocyte proliferation and induced higher levels of IL-12p70 and IFN-γ secretion. The peptide-pulsed DC vaccines significantly increased the proportion of CD8+ T cells among CTLs and mediated dose-dependent cytotoxic effects against pancreatic cancer cell lines (PANC-1, BXPC-3, MIA PaCa-2), with the highest efficacy observed in the MUC1 peptide 619 group. Bioinformatic analysis revealed that MUC1 was highly expressed in pancreatic cancer tissues and associated with poor patient prognosis. Western blot further confirmed MUC1 expression in pancreatic cancer cell lines. In vivo, the DC vaccine pulsed with peptide 619 significantly suppressed tumor growth (tumor weight inhibition rate: 51.4%), increased the percentage of CD8+ T cells in peripheral blood, and enhanced the infiltration of hCD45+ cells into tumor tissues.ConclusionMUC1 peptide-pulsed DCs effectively activate specific CTL responses, indicating that DC-based vaccine immunotherapy holds promise for the management of pancreatic cancer.